Implementasi Kebijakan Kepmendiknas Nomor: 044/U/2002 tentang Peran dan Fungsi Komite Sekolah di SMA Muhammadiyah 1 Gresik - Nur Hidajati (Universitas Muhammadiyah Malang, 2014)
Nur HidajatiGuru SMA Muhammadiyah 1 Gresike-mail: hidajatinur@gmail.comAbstract:This research used a qualitative descriptive approach. From the analysis, it can be found that: 1) Senior High School of Muhammadiyah 1 Gresik has responded the policy on the school committee issued by the government since the determination of legislation. The activity manifested by this educational institution is the establishment of official decision about the organization structure of the school committee periodically. They are having AD/ART (The constitution and bylaws) of school committee; meetings conducted by the committee administrators with the principal, as well as a signatory on the letters of external aid. 2) The supporters of the policy implementation about school committee are the participation of society and parents as an educational resource. The constraint on the policy implementation of school committee is the similarity of editorial between the regulation of school committee and the Primary and Secondary Education Council of Muhammadiyah. 3) The solutions to solve the problems in the implementation on the policy of the school committee Senior High School of Muhammadiyah 1 Gresik is the involvement of the school committee on public relations activitiesKeywords: policy, school committeeAbstrak:Penelitian ini menggunakan pendekatan deskriptif kualitatif. Dari analisis didapatkan bahwa: 1) SMA Muhammadiyah 1 Gresik telah merespon kebijakan tentang komite sekolah yang dikeluarkan oleh pemerintah sejak ditetapkannya peraturan. Aktivitas yang diwujudkan oleh lem-baga pendidikan tersebut adalah penetapan surat keputusan tentang struktur organisasi komite sekolah secara berkala; memiliki AD/ART komite sekolah; adanya pertemuan pertemuan yang dilakukan oleh pengurus komite dengan kepala sekolah; serta penandatangan surat surat pemberian bantuan dari pihak eksternal; 2) pendukung implementasi kebijakan tentang komite sekolah adalah partisipasi masyarakat dan orang tua sebagai sumber daya pendidikan dan kendala implementasi kebijakan tentang komite sekolah adalah adanya kesamaan redaksi antara peraturan komite sekolah dan Majelis Dikdasmen Muhammadiyah; 3) Solusi untuk mengatasi permasalah-an implementasi kebijakan komite sekolah di SMA Muhammadiyah 1 Gresik adalah pelibatan komite sekolah pada kegiatan bidang kerja kehumasan.Kata kunci: kebijakan, komite sekolah